Antibiotics impair murine hematopoiesis by depleting the intestinal microbiota - Josefsdottir, Kamilla S. (Blood, 2017)
Bone marrow suppression is an adverse effect associated with many antibiotics, especially when administered for prolonged treatment courses. Recent advances in our understanding of steady-state hematopoiesis have allowed us to explore the effects of antibiotics on hematopoietic progenitors in detail using a murine model. Antibiotic-treated mice exhibited anemia, thrombocytosis, and leukopenia, with pronounced pan-lymphopenia as demonstrated by flow cytometric analysis of peripheral blood. Bone marrow progenitor analysis revealed depletion of hematopoietic stem cells and multipotent progenitors across all subtypes. Granulocytes and B cells were also diminished in the bone marrow, whereas the number of CD8(+) T cells increased. Reductions in progenitor activity were not observed when cells were directly incubated with antibiotics, suggesting that these effects are indirect. Hematopoietic changes were associated with a significant contraction of the fecal microbiome and were partially rescued by fecal microbiota transfer. Further, mice raised in germ-free conditions had hematopoietic abnormalities similar to those seen in antibiotic-treated mice, and antibiotic therapy of germ-free mice caused no additional abnormalities. The effects of antibiotics were phenocopied in Stat1-deficient mice, with no additional suppression by antibiotics in these mice. We conclude that microbiome depletion as a result of broad-spectrum antibiotic treatment disrupts basal Stat1 signaling and alters T-cell homeostasis, leading to impaired progenitor maintenance and granulocyte maturation. Methods to preserve the microbiome may reduce the incidence of antibiotic-associated bone marrow suppression.